2005
DOI: 10.1111/j.1365-2036.2005.02476.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of Japanese patients with ulcer induced by low‐dose aspirin and other non‐steroidal anti‐inflammatory drugs

Abstract: Summary Background : The incidence and severity of non‐steroidal anti‐inflammatory drugs (NSAIDs)‐induced gastro‐duodenal ulcer have not been extensively studied in Japan. Aim : We performed a prospective study to clarify NSAIDs‐induced gastro‐duodenal injury, focusing especially on low‐dose aspirin (L‐A). Methods : Two hundred and thirty‐eight patients with bleeding peptic ulcers admitted to our hospital. History of taking NSAIDs and anti‐ulcer drugs was obtained from all patients who underwent endoscopic exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…In that study, the odds ratios for upper gastrointestinal bleeding were 5.5 for aspirin and 6.1 for non-aspirin NSAIDs (p \ 0.01), which indicates that, in Japan, aspirin and nonaspirin NSAIDs are major causes of upper gastrointestinal bleeding, as has been observed in Western countries. Another study indicated that approximately one-third of hospitalized patients with gastrointestinal bleeding showed an association with low-dose aspirin [29]. Surprisingly, 41% of the patients with NSAID-related bleeding ulcers in this study used low-dose aspirin.…”
Section: Discussionmentioning
confidence: 48%
“…In that study, the odds ratios for upper gastrointestinal bleeding were 5.5 for aspirin and 6.1 for non-aspirin NSAIDs (p \ 0.01), which indicates that, in Japan, aspirin and nonaspirin NSAIDs are major causes of upper gastrointestinal bleeding, as has been observed in Western countries. Another study indicated that approximately one-third of hospitalized patients with gastrointestinal bleeding showed an association with low-dose aspirin [29]. Surprisingly, 41% of the patients with NSAID-related bleeding ulcers in this study used low-dose aspirin.…”
Section: Discussionmentioning
confidence: 48%
“…During the last decade, PU bleeding did not significantly change (2,5,14), but the incidence increased in patients older than 75 years of age (15). In last decade, usage of non-steroidal anti-inflamatory drugs (NSAID) also increased, especially in the increasing elderly population (16,17). The use of NSAIDs is associated with an increased risk of bleeding ulcers (18,19).…”
Section: Original Articlementioning
confidence: 99%
“…Low-dose aspirin has also been shown to induce peptic ulcers, similar to the effects of regular-dose aspirin and other NSAIDs [1] ; this finding suggests that NSAIDinduced peptic ulcers may become more common among the elderly population, since many patients receive antithrombotic therapy using low-dose aspirin for the treatment of cardiovascular diseases. Previously, we reported that NSAIDs were associated with hemorrhagic peptic ulcers in 28% of the patients seen between 2001 and 2004; the rate of patients receiving low-dose aspirin in this population was 27%, while the rates of patients receiving regular-dose aspirin, loxoprofen, diclofenac and other NSAIDs were 6%, 16%, 10% and 21%, respectively [1] . These data suggest that among the various NSAIDs in use, low-dose aspirin is the most important drug provoking peptic ulcers in Japan.…”
Section: Introductionmentioning
confidence: 77%
“…According to our previous survey [1] , a total of 82% of patients with hemorrhagic peptic ulcers tested positive for H pylori infection; the positivity rate was higher among those not treated with NSAIDs (88.6%) than among those receiving NSAIDs (67.2%). Of note, 62.5% of the patients with hemorrhagic peptic ulcers induced by lowdose aspirin tested positive for H pylori [1] . However, whether H pylori eradication prevents the development of peptic ulcers induced by low-dose aspirin remains controversial [2] .…”
Section: Introductionmentioning
confidence: 99%